2014
DOI: 10.1155/2014/175693
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes and Serum Ghrelin Level in Patients with Psoriasis

Abstract: Background. Serum ghrelin levels may be related to metabolic and clinical changes in patients with psoriasis. Objective. This study was performed to determine the possible effects of serum ghrelin in patients with psoriasis. Methods. The study population consisted of 25 patients with plaque psoriasis. The patients were questioned with regard to age, gender, age of onset, duration of disease, height, weight, and body mass index (BMI). In addition, fasting blood sugar, triglyceride, cholesterol levels, insulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Ghrelin can antagonize the insulin system [ 118 ] and there is a negative correlation between severity of psoriasis and ghrelin level [ 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ghrelin can antagonize the insulin system [ 118 ] and there is a negative correlation between severity of psoriasis and ghrelin level [ 119 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, significantly lower ghrelin levels in BD patients, and also in active BD patients could be explained by elevated cytokine levels in BD patients. Few studies reported a negative correlation between ghrelin levels and the severity of psoriasis [35, 38]. Similarly, Koca et al [27] stated that inflammation and cytokines could be a reason for lower ghrelin levels in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Extensively studied adipokines in serum and plasma were resistin, leptin, adiponectin, ghrelin, and retinol binding protein-4 (RBP-4). With the exception of adiponectin, all serum and plasma adipokine levels were significantly higher in psoriasis versus healthy individuals [76,79,[82][83][84][85][86]88]. Only serum resistin levels correlated weakly with PASI (r 2 = 0.027) and none of the adipokines consistently showed a normalization in levels after effective treatment [76,80,81,83,86,87] Growth factors are involved in angiogenesis and hypervascularity in psoriasis and are well studied as biomarkers.…”
Section: Serum Biomarkers In Psoriasismentioning
confidence: 99%